KEMAMPUAN SINTESIS MATEMATIS MAHASISWA DITINJAU DARI IDENTITAS GENDER: Student's Mathematic Synthesis Ability From Gender Identity - Rahmat Winata; Sugiharto Sugiharto; Yupito Yupito (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to describe the mathematical synthesis ability of students of Mathematics Education at the University of Palangka Raya in terms of masculine and feminine gender identities. The type of research is qualitative research. The research subjects were 4 second semester students of mathematics education consisting of 2 students each with a masculine or feminine gender identity. Determination of the subject using purposive sampling. For data collection, the method of questionnaires, tests, and interviews was used. Data validity using triangulation method. The results of this study are students with feminine gender identity have good mathematical synthesis skills because they meet the three indicators of mathematical synthesis ability, namely finding theories or relationships, predicting, and evaluating. Meanwhile, students with masculine gender identity have mathematical synthesis abilities that are not good enough, because even though they can meet the indicators of finding theories or relationships and evaluating, students with masculine gender identities fail to carry out plans and the settlement process properly, resulting in errors in problem solving.